Level of agreement between adolescents' self‐assessment and parent proxy report of health‐related quality of life in adolescents with sickle cell disease. Issue 4 (5th February 2020) - Blake, Alphanso; Guthrie‐Dixon, Natalie; Grindley, Marlyn; Barton‐Gooden, Antoinette; Knight‐Madden, Jennifer; Asnani, Monika
Abstract: Background: We aim to assess the levels of agreement between parents, as proxies, and Jamaican adolescents living with sickle cell disease (SCD) in the reporting of the adolescent's quality of life. Procedures: This cross‐sectional study assessed 102 patient/proxy pairs on quality of life of adolescents with SCD using the PedsQL‐SCD module. The level of agreement among pairs was assessed starting with broad group‐level approaches (the Wilcoxon signed‐rank test augmented by exploring percentage agreement) tapering to individual‐level approaches (intraclass correlation coefficients [ICCs] supplemented with Bland‐Altman plots). Results: Most patients (76.5%) had homozygous SS disease (45.1% females; mean age 15.2 ± 1.5 years). Median total pediatric quality of life (PedsQL) scores were 79.1 (adolescent report) and 80.2 (parental report) ( P = .60). There were 11.8% underestimation and 12.7% overestimation of overall health‐related quality of life (HRQOL) by parents. The highest perfect agreement existed on the "pain and hurt" domain for both male and female adolescents (85.7% and 84.4%, respectively). Overestimation was highest on the "social communication" domain for both male and female adolescents (19.6% and 34.8%, respectively). Parents exhibited good agreement on total PedsQL scores in male adolescents (ICC = 0.70), but moderate agreement (ICC = 0.43) in female adolescents. Generally, parents underestimated their male child's functioning and overestimated the female child's functioning on the various domains. Conclusions: Parents and adolescents exhibit fair agreement in assessment of the adolescent's overall HRQOL but differ on subjective domains. Agreement varies by sex of the affected teen where girls' HRQOL is generally overestimated by the parental proxy. Interventions to improve parents' understanding of their children's psychosocial needs are needed.